Breaking the Binary Oppositions of the Interior: A Momentary Permanence - Adams, Roderick; Marlor, Lucy (UI Scholars Hub, 2019)
The previously static view of the interior is changing, as social, economic and cultural factors produce a new requirement for building flexibility and potentially forcing a change to the normal spatial paradigms. There is an emerging altered dynamic between building, interior and user, posing the question – when does architecture become the interior? Conceptions of the future interior give renewed focus to the more flexible void space, over the opposing static architectural shell. By adjusting the realms of contact within a space and limiting the influence of architecture, the user is re-envisioned as a central adjudicator of spatial experience. Provocatively, conceiving the interior as a more temporal or fluid entity, we may liberate its relationship with its immovable and constant architectural keeper. This paper will argue the dynamic city structure is driving a new conception of the interior and its place within society and architecture.